Glial injury in neurotoxicity after pediatric CD19‐directed chimeric antigen receptor T cell therapy. Issue 1 (27th May 2019) - Gust, Juliane; Finney, Olivia C.; Li, Daniel; Brakke, Hannah M.; Hicks, Roxana M.; Futrell, Robert B.; Gamble, Danielle N.; Rawlings‐Rhea, Stephanie D.; Khalatbari, Hedieh K.; Ishak, Gisele E.; Duncan, Virginia E.; Hevner, Robert F.; et al.
Abstract : Objective: To test whether systemic cytokine release is associated with central nervous system inflammatory responses and glial injury in immune effector cell‐associated neurotoxicity syndrome (ICANS) after chimeric antigen receptor (CAR)‐T cell therapy in children and young adults. Methods: We performed a prospective cohort study of clinical manifestations as well as imaging, pathology, CSF, and blood biomarkers on 43 subjects ages 1 to 25 who received CD19‐directed CAR/T cells for acute lymphoblastic leukemia (ALL). Results: Neurotoxicity occurred in 19 of 43 (44%) subjects. Nine subjects (21%) had CTCAE grade 3 or 4 neurological symptoms, with no neurotoxicity‐related deaths. Reversible delirium, headache, decreased level of consciousness, tremor, and seizures were most commonly observed. Cornell Assessment of Pediatric Delirium (CAPD) scores ≥9 had 94% sensitivity and 33% specificity for grade ≥3 neurotoxicity, and 91% sensitivity and 72% specificity for grade ≥2 neurotoxicity. Neurotoxicity correlated with severity of cytokine release syndrome, abnormal past brain magnetic resonance imaging (MRI), and higher peak CAR‐T cell numbers in blood, but not cerebrospinal fluid (CSF). CSF levels of S100 calcium‐binding protein B and glial fibrillary acidic protein increased during neurotoxicity, indicating astrocyte injury. There were concomitant increases in CSF white blood cells, protein, interferon‐γ (IFNγ), interleukin (IL)‐6, IL‐10, and granzyme B (GzB), with concurrent elevation of serum IFNγ IL‐10, GzB, granulocyte macrophage colony‐stimulating factor, macrophage inflammatory protein 1 alpha, and tumor necrosis factor alpha, but not IL‐6. We did not find direct evidence of endothelial activation. Interpretation: Our data are most consistent with ICANS as a syndrome of systemic inflammation, which affects the brain through compromise of the neurovascular unit and astrocyte injury. ANN NEUROL 2019